Domination Defect of Some Parameterized Families of Graphs - Miranda, Aldwin T.; Eballe, Rolito G. (Communications in Mathematics and Applications, 2024)
In this paper, we study the concept of \(k\)-domination defect of a graph \(G\) and investigate it for some parameterized families of graphs. We produce characterizations of the \(ζ_k\)-sets of the path, cycle, centipede graph, sunlet graph, bi-star graph, crown graph, and complete bipartite graph, and then from these characterizations, the corresponding \(k\)-domination defects of the aforesaid graphs are determined.